2001
DOI: 10.1016/s0014-5793(01)02359-6
|View full text |Cite
|
Sign up to set email alerts
|

Rab4 affects both recycling and degradative endosomal trafficking

Abstract: The small GTPases Rab4, Rab5 and Rab7 are endosomal proteins which play important roles in the regulation of various stages of endosomal trafficking. Rab4 and Rab5 have both been localized to early endosomes and have been shown to control recycling and endosomal fusion, respectively. Rab7, a marker of the late endosomal compartment, is involved in the regulation of the late endocytic pathway. Here, we compare the role of Rab4, Rab5 and Rab7 in early and late endosomal trafficking in HeLa cells monitoring ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 47 publications
15
125
2
Order By: Relevance
“…These results contrast with studies of Rab4, a protein associated with recycling from basolateral early endosomes (Sheff et al, 1999) in which expression of a GTP-binding mutant decreased the rate of Tf recycling (McCaffrey et al, 2001). Although the inhibition of recycling induced by expression of the mutant Rab4 indicates that Rab4 is necessary for recycling, the enhanced recycling induced by expression of mutant Rab10 suggests that Rab10 somehow negatively regulates recycling from basolateral sorting endosomes.…”
Section: Rab10 Mediates Transport From Basolateral Sorting Endosomes contrasting
confidence: 85%
See 1 more Smart Citation
“…These results contrast with studies of Rab4, a protein associated with recycling from basolateral early endosomes (Sheff et al, 1999) in which expression of a GTP-binding mutant decreased the rate of Tf recycling (McCaffrey et al, 2001). Although the inhibition of recycling induced by expression of the mutant Rab4 indicates that Rab4 is necessary for recycling, the enhanced recycling induced by expression of mutant Rab10 suggests that Rab10 somehow negatively regulates recycling from basolateral sorting endosomes.…”
Section: Rab10 Mediates Transport From Basolateral Sorting Endosomes contrasting
confidence: 85%
“…The corresponding mutations in Ras, Rab7, Rab8, Rab11a, and Rab25 have been shown to decrease the affinity of the protein for GTP, resulting in the accumulation of a GDP-bound form (Feig and Cooper, 1988;Peranen et al, 1996;Bucci et al, 2000;Wang et al, 2000). This mutation frequently results in a protein with dominant-negative effects on Rab function; overexpression has been found to alter the function of Rab8 (Moritz et al, 2001) and yeast Sec4p (Walworth et al, 1989), as well as Rab4 (McCaffrey et al, 2001), Rab5 , Rab7 (Feng et al, 1995;Bucci et al, 2000), Rab11 (Ullrich et al, 1996;Wang et al, 2000a), Rab14 (Jununtula et al, 2004), and Rab15 (Zuk and Elferink, 2000). A second mutant was also created, encoding a change from glutamine into leucine at position 68 (Q68L).…”
Section: Mutations In the Gtp-binding And Gtp-hydrolysis Domains Altementioning
confidence: 99%
“…Our cloned Rab4a sequence was identical to the reported rat Rab4a sequence in the NCBI data base (accession number P05714) with the exception of two differences: Q47S and T75R. These two amino acids in our sequence (Ser 47 ) and (Arg 75 ) are conserved in the mouse and human sequences reported in the NCBI data base (accession numbers NP_033029 and NP_004569, respectively). Therefore, these two differences probably correspond to sequencing errors in the previously reported rat sequence.…”
Section: Methodssupporting
confidence: 67%
“…For example, rab5a is present on endosomes, is involved in endosome-endosome fusion (Gournier et al, 1998), in linking early endosomes to microtubules, and in minus-end-directed movement (Nielsen et al, 1999), although rab5a has not yet been demonstrated to interact with any motor protein. Rab 4 and rab 11 are endosome-associated proteins thought to be involved in recycling (Van Der Sluijs et al, 1991;McCaffrey et al, 2001;Peden et al, 2004) but their precise roles and which of the many possible effectors are relevant for this function remains unclear (Nagelkerken et al, 2000;Cormont et al, 2001;van der Sluijs et al, 2001;Fouraux et al, 2004;Peden et al, 2004). The present data suggest that hrs may link endosomes to actin through actinin-4, BERP, and myosin Vb.…”
Section: Discussionmentioning
confidence: 60%